Development and tribological characterisation of nanostructured Zn-Ni and Zn-Co coatings: a comparative study. (4th July 2018) - Nasri, F.; Zouari, M.; Kharrat, M.; Dammak, M.; Vacandio, F.; Eyraud, M.
ABSTRACT: Zn-Ni and Zn-Co alloy coatings were electrodeposited on mild steel from sulphate-based baths. The morphology, microstructure, microhardness and tribological behaviours of the coatings have been studied and discussed. While the Zn-5wt-% Co layers presented a nanocrystalline simple nodular structure (45 ± 5 nm), the Zn-14wt-% Ni showed a particular structure called cauliflower morphology (30 ± 7 nm). The X-ray diffraction analysis showed that each of the electrodeposits was formed from zinc solid solution with a uniform zinc-cobalt intermetallic phase γ2 (CoZn13 ) for Zn-5wt-% Co alloy. However, a single γ-phase (intermetallic compound Ni5 Zn21 ) was presented for the Zn-14wt-% Ni alloys. The Zn-14wt-% Ni films were found to be harder and rougher than the Zn-5wt-% Co layers. Plastic deformation and oxide layers production were the main wear mechanisms for the investigated coatings. The Zn-14wt-% Ni coatings were found to have the best wear resistance due to their microhardness and particular structure.